POLLINATION POTENTIAL OF STINGLESS BEES (TRIGONA LAEVICEPS) FOR MAURITIAN RASBERRY (RUBUS ROSIFOLIUS) CULTIVATION - Tanu Dewangga, Rezha
of the rapid fruiting cycle and its ability to produce fruit throughout the year. One influential factor is the success of fruit formation through the process of pollination. Several previous studies in the area of origin of this plant showed that this plant has a poor selfpollination ability so it requires pollinating agents, especially insects. In the cultivation process, there are 3 main sources of pollinating agents, namely wild insects, domesticated insects, and humans. This is the basis of this study which aims to obtain information about the mechanism of pollination on Mauritian raspberry plants related to the proportion of fruit formation and quality of fruit (in the form of fruit volume). In this study the effectiveness of 4 pollination models was observed, namely Autopolination (A); wild insects (SL); Local Stingless bee (Tetragonula laeviceps) (SB); and Humans (M). Observations on insect pollination include the level of visits, handling time, and natural polinator guilds obtained through direct observation. The results showed the level of visits from other insects ranged between 0700 - 1300 and peak at 1000-1100. Handling time of other insects ranged from 2-7 seconds. Stingless bee visit rates start at 07.00 - 16.00 with a peak at 1300 - 1400 and an average handling time of 13.6 seconds. For production, pollination success and fruit quality of SB treatment is the highest compared to other treatments (P <0.05) by 96% and 3.928 cm3. Thus, T. laeviceps is considered to have good potential as a pollinating agent of R. rosifolius.